PELATIHAN SIKLUS AKUNTANSI DAN JURNAL UMUM PADA SISWA-SISWI SMK SANDIKTA - Kurniawati, Herni; Ratna Niandra; Esther Dharmadi Santoso (Jurnal Serina Abdimas, 2025)
Community Service (PKM) was carried out to help students of SMK Sandikta Bekasi understand the accounting cycle and its stages well. The accounting cycle is a series of accounting processes carried out periodically, consisting of ten stages: (a) identification and analysis of business transactions; (b) journalizing transactions; (c) posting to the ledger;(d) preparing a trial balance; (e) journalizing and posting adjusting entries; (f) preparing an adjusted trial balance,;(g) preparing financial statements;(h) journalizing and posting closing entries; (i) preparing a post-closing trial balance; and (j) preparing reversing entries. PKM uses primary data obtained directly from SMK Sandikta, such as data from interviews with the principal and teachers, concluding that this PKM uses descriptive qualitative data. Meanwhile, secondary data was obtained from books, journals, and the internet that support this research. PKM was conducted using an introductory method to the Partners, followed by presenting the material in printout form created in Microsoft PowerPoint and distributed to approximately 30 students. After presenting the material, students were given time to ask questions to better understand the content. The result of the PKM is that the partner feels they have a better understanding of the accounting cycle material and the general journal provided, and the partner requested to conduct PKM again in the next semester with advanced material, namely how to post transaction journals and create a trial balance. The output of this PKM result is the proceedings of the national seminar as a speaker and the national PKM journal article, as well as Intellectual Property Rights. ABSTRAK Pengabdian Kepada Masyarakat (PKM) diilaksanakan membantu siswa-siswi SMK Sandikta Bekasi dapat memahami siklus Akuntansi dan tahapannya dengan baik. Siklus akuntansi adalah serangkaian proses akuntansi yang dilakukan secara periodik, dengan sepuluh tahapan, terdiri dari (a) identifikasi dan analisis transaksi bisnis; (b) menjurnal transaksi; (c) memposting ke buku besar; (d) membuat neraca saldo; (e) menjurnal dan posting jurnal penyesuaian; (f) membuat neraca saldo setelah penyesuaian; (g) membuat laporan keuangan; (h) menjurnal dan posting jurnal penutup; (i) membuat neraca saldo setelah penutupan; dan (j) membuat jurnal pembalik. PKM menggunakan data primer yang diperoleh langsung dari pihak SMK Sandikta seperti data hasil wawancara dengan kepala sekolah dan guru sehingga disimpulkan bahwa PKM ini menggunakan data kualitatif deskriptif. Sedangkan untuk data sekunder diperoleh dari buku, jurnal, internet yang mendukung penelitian ini. PKM dilaksanakan dengan metode perkenalan terlebih dahulu kepada Mitra, dengan dilanjutkan memaparkan materi berbentuk print out yang dibuat dalam Microsoft Power Point dan dibagikan kepada Mitra sebanyak kurang lebih 30 siswa. Setelah memaparkan materi, diberikan waktu kepada siswa untuk bertanya agar lebih memahami materi. Hasil dari PKM adalah Mitra merasakan lebih memahami materi siklusakuntansi dan jurnal umum yang diberikan, dan Mitra meminta untuk dilakukan kembali PKM di semester berikutnya dengan materi lanjutan yaitu bagaimana memposting jurnal transaksi dan membuat neraca saldo. Hasil PKM ini menghasilkan pemakalah seminar nasional, aritkel di jurnal nasional PKM, dan Hak Kekayaan Intelektual.